The ongoing conservation of the Ghent Altarpiece 2012-2015 - Anne Van Grevenstein (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The Ghent altarpiece has survived a traumatic history and succesive treatments in the past have left their traces. The interdisciplinary approach to the treatment in 1950-51, is still exemplary for the present campaign, started by a team of IRPA in 2012. Roger Marijnissen participated in the research and followed closely both treatments.